Making ends meet in financial scarcity in old age - Rikke Nøhr Brünner (International Journal of Ageing and Later Life, 2018)
The purpose of this paper is to explore qualitatively how older people (aged 69–85 years) living in relative poverty experience their daily life and how they make ends meet (N = 16). The empirical analysis shows that despite deprivations, the interviewees are mostly satisfied, and in order to analytically understand this satisfaction I draw on three individual and structural aspects: (1) The Danish welfare state ensures the interviewees’ basic ontological safety. (2) As the interviewees lived in financial scarcity during other phases of their lives, they are familiar with being thrifty, and they have a practical sense of making ends meet. (3) Although none of the interviewees had saved up for their retirement, some had saved up social capital, which enables them to modify or take a break from financial scarcity. Thus, although the interviewees’ financial capabilities are similar, their actual daily lives are very different from each other.